Réponses

2014-09-03T14:33:16+02:00
A = 9/7 + 3 x 11/4 - 1
A = 9/7 + 33/4 - 1
A = 9 x 4 / 7 x 4 + 33 x 7 / 4 x 7 - 1 x 28 / 1 x 28
A = 36/25 + 231/28 - 28/28
A = 239/28

B = (7/11 - 5/3) / 19/22
B = (7 x 3 / 11 x 3 - 5 x 11 / 3 x 11) / 19/22
B = 21/33 - 55/33 / 19/22
B = 34/33 : 19/22
B = 34/33 x 22/19
B = 748/627
B = 11 x 68 / 11 x 57
B = 68/57

C = (8/7 - 7/8) (1/3 - 3)

C = 8/21 - 23/7 - 7/24 + 21/8
C = 8/21 - 23 x 3 / 7 x 3 - 7/24 + 21/8
C = 8/21 - 69/21 - 7/24 + 21/8
C = - 61/21 - 7/24 + 21/8
C = - 61 x 8 / 21 x 8 - 7 x 7 / 24 x 7 + 21 x 21 / 8 x 21
C = - 488/168 - 49/168 + 441/168
C = - 96/168
C = 24 x - 4 / 24 x 7
C = - 4/7